Comparison of peak expiratory flow measurement by Mini-Wright peak flow meter and electronic spirometer in healthy elementary school children - Mardjanis Said; Sudigdo Sastroasmoro; Bambang Supriyatno; Yovita Ananta (Indonesian Pediatric Society, 2004)
Objective This study aims to compare peak expiratory flow mea-surement by peak flow meter and electronic spirometer in healthyelementary school children.Methods This was a cross-sectional study performed in an el-ementary school near Cipto Mangunkusumo hospital (SDNPegangsaan 01). The study group consisted of healthy childrenaged 6-12 year old. Data regarding identity and history of illnesswas taken in each subject. Routine physical examination was per-formed and recorded. Each subject performed lung function testsby means of electronic spirometer AS-7 as well as by Mini-Wrightpeak flow meter. The subject should perform a minimum of threemaneuvers for each method where only the best result was re-corded. Method comparison test to assess agreement betweentwo methods was employed in this study.Results There were 10 males and 15 females enrolled in this study.None of the subjects currently have any respiratory symptoms andsigns. This study found that the mean peak expiratory flow (PEF) byspirometer was 226.8Â±73.13 L/min while by peak flow meter was223.0Â±45.05. Mean difference between spirometer and peak flowmeter measurements is 6.2 with standard deviation of 60.82. Thesevalues resulted in limits of agreement of -115.44 to +127.84 L/min.Conclusions This study finds disagreement between electronicspirometer and Mini-Wright peak flow meter in measuring peakexpiratory flow, therefore these two devices cannot be usedinterchangeably. Mini-Wright peak flow meter still has a role inhome monitoring, but the physician should interpret the resultscarefully.